Enriching maritime vocational education with physical-sports activities - Marudut Bernadtua Simanjuntak; Marihot Simanjuntak; Vidya Selasdini; Meilinasari Nurhasanah Hutagaol; April Gunawan Malau; Susi Herawati; Pargaulan Dwikora Simanjuntak; Damoyanto Purba; Derma Watty Sihombing (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective: The maritime sector increasingly acknowledges the vital role of physical-sports activities in enhancing the health and well-being of its workforce. This study investigates how physical-sports activities can be effectively integrated into maritime vocational education to improve health outcomes and professional readiness among maritime professionals in Indonesia.